2013
DOI: 10.1007/s00405-013-2598-6
|View full text |Cite
|
Sign up to set email alerts
|

Management of intractable epistaxis in patients who received radiation therapy for nasopharyngeal carcinoma

Abstract: To report clinical manifestations, bleeding point localization, and outcomes of management in 16 patients with 16 instances of intractable epistaxis after radiation therapy for nasopharyngeal carcinoma. Retrospective chart review of 16 patients with nasopharyngeal carcinoma (mean age 52.06 ± 14.37 years) with 16 instances of intractable epistaxis during the past 5 years, whose diagnosis was confirmed by angiography (n = 10) or MRI/CT imaging studies and clinical manifestations (n = 6). The mean radiation dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 7 publications
(6 reference statements)
1
38
0
Order By: Relevance
“…15 However, He et al reported that concerning stent erosion and infection because of local inflamed and necrotic tissue, as well as a lack of antiplatelet preparation, the main trunk occlusion should be thought as the preferred treatment toward, if feasible. 7 In our experience, we agree with He's opinion because most of the lesion vessels are significantly poor and the coils are the common embolized agents that can be used in emergent situations. But in some situations where the patients' hemodynamics are stable and the lesion vessels are not so much poor, the covered stents can be considered to be used.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…15 However, He et al reported that concerning stent erosion and infection because of local inflamed and necrotic tissue, as well as a lack of antiplatelet preparation, the main trunk occlusion should be thought as the preferred treatment toward, if feasible. 7 In our experience, we agree with He's opinion because most of the lesion vessels are significantly poor and the coils are the common embolized agents that can be used in emergent situations. But in some situations where the patients' hemodynamics are stable and the lesion vessels are not so much poor, the covered stents can be considered to be used.…”
supporting
confidence: 78%
“…5 Endovascular treatment has been recommended as the first-line treatment modality by some doctors because angiography can detect the bleeding vessels quickly and accurately and endovascular embolization has a high success rate, especially for patients with a ruptured pseudoaneurysm in the internal carotid which is a significant catastrophic condition. 7,[13][14][15] In our study, twenty-three patients (95.8%) were successfully treated by one-time or two-time endovascular embolization, which showed a great efficacy of endovascular treatment of nasopharyngeal hemorrhage after radiotherapy for NPC. One patient died of abrupt massive hemorrhage (case 1) and three patients had re-bleeding (case 2, case 4, case 5).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…First, quick and effective measures are very important for hemorrhage rescue, but treatments of massive nasopharyngeal bleeding varied considering expense, distance, and clinical medical condition. Massive nasopharyngeal bleeding involving the internal maxillary artery could be rescued with effective treatment, such as hemostasis by gelatin sponge compression, nasopharyngeal packing, artery ligation, and other surgical measures [ 32 ]. However, carotid artery rupture is a common result of LNN, which results in a high mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, endovascular treatment has provided an effective way to control the bleeding associated with carotid blowout syndrome. In previous works, some researchers have suggested that stent placement is safe and feasible for this disease (Hakime et al 2013 ; Farivar et al 2014 ), and some argued that endovascular embolization provides both safe and effective management (He et al 2013 ). Additionally, some researchers have found that there was no significant difference in the technical and hemostatic outcomes of stent placement and endovascular embolization (Chang et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%